Characterization of the transcriptional trans activator of human foamy retrovirus. - Keller, A (1991)
The human foamy viruses, or spumaviruses, a distinct subfamily of complex human retroviruses, remain poorly understood both in terms of their pathogenic potential and in terms of the regulatory mechanisms that govern their replication. Here, we demonstrate that the human spumaretrovirus shares with other complex human retroviruses the property of encoding a transcriptional trans activator of the homologous viral long terminal repeat. This regulatory protein is encoded by the viral Bel-1 open reading frame and is localized to the nucleus of expressing cells. The Bel-1 trans activator is shown to function effectively in cell lines derived from human, simian, murine, and avian sources. The viral target sequence for Bel-1 has been mapped 5' to the start of viral transcription and is therefore likely to be recognized as a DNA sequence. Our results further suggest that the mechanism of action of the Bel-1 protein may be distinct from those reported for the transcriptional trans activators encoded by members of the other human retroviral subfamilies.